Canine Ocular Transmissible Venereal Tumour - A Report of Four Cases - K S, Rugmini; S, Subapriya; Raj H, Pushkin; Rao, Ganne Venkata Sudhakar; S, Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine Transmissible Venereal tumour (TVT) or Sticker’s sarcoma is a sexually transmitted neoplasm which is  endemic in tropical and subtropical countries. The tumor  is transmitted between dogs through direct skin contact,  licking and bite injuries (Kabuusu et al., 2010). External  genitalia are the frequent location for TVT. It can also occur  in areas such as the oral cavity, nasal cavity, skin, sclera,  and anterior chamber of the eye. Tumor cell inoculation  is also possible in extragenital primary sites, such as the  nasal and oral cavities, rectum, skin, and ocular membranes  (conjunctiva), via licking or sniffing of the vaginal and/or  the preputial discharge. TVT is further characterized by a  unique feature wherein the mutated tumor cell itself acts as  the causative agent and propagates within the implanted  host (Ganguly et al., 2016). The present report describes the  extraocular and intraocular manifestations of TVT in dogs  and its response to treatment.
Keywords: canine; Transmissible venereal tumour; TVT; intrauveal tumor; ocular tumor; Vincristine